Condições de vida de ribeirinhos do Amazonas - Mata, Geraldo Júnior Menezes da (Brasil, 2023)
This study describes socioeconomic, demographic and access to work characteristics of riverside dwellers in the middle Amazon, Brazil. This is a cross-sectional study, in households in the rural area of the municipality of Itapiranga, located in the hydrographic basin of the Amazon River, from August to November 2021, with a census sample of households. The respective variables were selected, namely: Sociodemographic and work characteristics of the head of the household and access to public services. The study included 160 households belonging to the riverside communities of Nossa Senhora do Rosário, São João, São José da Enseada, Lago do Coró, Monte Sião, Inajatuba and Santa Maria. Most homes were built of masonry, with electricity, only 8,13% had access to piped water supplied by the general distribution network, using a well and spring (81,25%) as the main source of access to water, without access to public sewage. Family income is two minimum (96,87%) and the most frequent classes among these families were D and E (96.87%). Most households were headed by males 73,75, with a mean age of 45,49 years (Standard Deviation-SD=14.90), self-declared brown, single, with complete secondary education, although a percentage of next next who self-declared illiterate and/or with only incomplete primary education. Reflected in the work situation, the informed majority did not have a formal employment relationship. There is an important scenario of social vulnerability and deprivation of access to public services and work experienced by riverside people in the municipality of Itapiranga.